COMFORT CHARACTER OF LANDSCAPE FEATURES OF TRADITIONAL STREETS IN AMMAN, JORDAN - Alamoush, Saja Jamil; Jaafar, Nor Haslina; Mohd Husini, Elina; Wan Ismail, Wan Norisma (PLANNING MALAYSIA, 2018)
Fast expanding of urban development changes the street function and gives priority for vehicles, which effects the urban fabric and cultural life of the city. It makes walking in the street difficult and uncomfortable. Hence, this research aims to explore the influence of landscape features towards comfort character of traditional streets in Amman, Jordan. The case study was Rainbow Street in Amman, the capital city in Jordan. Mixed-method approach was used in this study, which involved direct observation (visual and behavioural) and user perception (survey and in-depth interviews) techniques. The data was analysed through thematic analyses for qualitative data and descriptive statistics for quantitative data. The results show that landscape features that contribute towards comfort character could be divided into two main categories, namely, pedestrian amenities and sidewalk. This should be taken into consideration in the design of the existing and future streets in Jordan.